2013
DOI: 10.1007/s00423-013-1145-7
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal papillary thyroid carcinoma—a consensus report of the European Society of Endocrine Surgeons (ESES)

Abstract: MPTC could be the result of either true multicentricity or intrathyroidal metastasis from a single malignant focus. Radiation and familial nonmedullary thyroid carcinoma are conditions at risk of MPTC development. The prognostic importance of multifocal tumor growth in PTC remains controversial. Prognosis might be impaired in clinical MPTC but less or none in MPTC <1 cm. MPTC can be diagnosed preoperatively by FNAB and US, with low sensitivity for MPTC <1 cm. Total or near-total thyroidectomy is indicated to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 99 publications
5
68
1
2
Order By: Relevance
“…However, more data are required regarding the long-term therapeutic outcomes of multifocal PTC in microcarcinoma or larger tumors, as well as how unilateral or bilateral tumors and the number of tumors in multifocal carcinoma may affect treatment outcomes [1, 17]. Our study response to the consensus report of the European Society of Endocrine Surgeons suggests that prognosis might be impaired in clinical multifocal PTC, but the effect might be less or none in tumors < 1 cm [18]. Our results showed that multifocal papillary microcarcinoma had a lower relapse rate than larger tumors; however, there were no statistically significant differences in cancer and overall mortality after a mean follow-up of 7.1 ± 5.3 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, more data are required regarding the long-term therapeutic outcomes of multifocal PTC in microcarcinoma or larger tumors, as well as how unilateral or bilateral tumors and the number of tumors in multifocal carcinoma may affect treatment outcomes [1, 17]. Our study response to the consensus report of the European Society of Endocrine Surgeons suggests that prognosis might be impaired in clinical multifocal PTC, but the effect might be less or none in tumors < 1 cm [18]. Our results showed that multifocal papillary microcarcinoma had a lower relapse rate than larger tumors; however, there were no statistically significant differences in cancer and overall mortality after a mean follow-up of 7.1 ± 5.3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings cannot justify total thyroidectomy for all of the patients with solitary PTC on ultrasound. However, because the patients in our series had clinically advanced PTC, some of the occult nodules could be the source of recurrence, reported as multiple synchronous tumors or intrathyroidal metastasis (Mazzaferri & Jhiang 1994, Hay et al 2002, Bilimoria et al 2007, Iacobone et al 2014. Problems inherent to current diagnostic modalities (ultrasound and fine-needle aspiration cytology) complicate decisions regarding the extent of the initial thyroid surgery and underscore the need to identify clinicopathologic parameters predictive of multifocal disease.…”
Section: Discussionmentioning
confidence: 99%
“…According to a consensus report of the European Society of Endocrine Surgeons, they recommended bilateral prophylactic CLND for patients with total tumor diameter (sum of the largest diameter of all foci) greater than 1 cm, because the frequency of subclinical CLNM is higher in multifocal PTC. Combining literatures on multifocal PTC and our study, we believe TT should be considered for UMPTMC, especially with male gender and total tumor diameter greater than 1 cm [6]. …”
Section: Discussionmentioning
confidence: 71%
“…Total thyroidectomy (TT) is performed when the nodule is preoperatively confirmed to be malignant in bilateral lobes by FNAC [5]. Nevertheless, as the 17–87% of PTC were multifocal [6], there were different opinions on how to manage the unilateral multifocal PTMC (UMPTMC). Most surgeons prefer to proceed with TT, which would be associated with the lowest risk of locoregional recurrence.…”
Section: Introductionmentioning
confidence: 99%